PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA EXPEDISI DI PEKANBARU (Studi PT. JNE (Jalur Nugraha Ekakurir) Pekanbaru) - Hanna Ester Novia; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Problems hearts Research singer is whether the quality of service and price effect Satisfaction of customers, as for the purpose Of Research Singer is to review determine the effect of service quality and price of Satisfaction of customers (Study PT. JNE (JNE) Pekanbaru. quality service and price as a variable (X1, X2) meanwhile customer satisfaction as the dependent variable (Y).The problem in this research is the number of customers who experienced fluctuations in Pekanbaru JNE, and in the last 4 years are not achieving the target of only acquired in 2013. The research sample taken as many as 93 respondents from the population is calculated using the formula slovin. Data obtained from the questionnaire and subsequently processed to then be tested with statistics through SPSS.From the results of tests carried out showed that the quality of service and price positive and significant impact on customer satisfaction at PT. JNE (Line NugrahaEkakurir) Pekanbaru. Data analysis method used is multiple linear regression analysis and partial regression analysis.Keywords: Service Quality, Price, Customer Satisfaction